2006
DOI: 10.1177/0361198106198300107
|View full text |Cite
|
Sign up to set email alerts
|

Use of Gas Cushions for Field Measurement and Analysis of Hybrid Vibration Isolation Wall

Abstract: Ground vibration induced by traffic, such as occurs on roads, highways, and railroads, may become a nuisance to nearby inhabitants and buildings. These problems have recently increased, especially in urban areas as higher environmental quality is required. Although many efforts have been made to mitigate ground vibration, in some cases, more powerful measures are needed. In this paper, a three-layered hybrid-type vibration isolation wall that uses gas cushions was developed. To confirm the vibration isolation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…They are typically filled using a low density material (e.g. gas cushion [169] or polyurethane [170]) to increase the reflection coefficient between the soil and the trench, thus increasing its effectiveness. Essentially, the backfill should be of a low acoustic impedance compared to the background soil.…”
Section: Mitigation Of Ground Vibrationmentioning
confidence: 99%
“…They are typically filled using a low density material (e.g. gas cushion [169] or polyurethane [170]) to increase the reflection coefficient between the soil and the trench, thus increasing its effectiveness. Essentially, the backfill should be of a low acoustic impedance compared to the background soil.…”
Section: Mitigation Of Ground Vibrationmentioning
confidence: 99%
“…This is physically impractical as trenches require in-fill material for safety and stability criteria. A common engineering solution is to fill trenches with low density gas cushions [34] or polyurethane [13]. Rather than introduce additional approximations for in-fill material properties it was found that open trenches provided an effective condition under which to analyze trench geometry.…”
Section: Trench Modellingmentioning
confidence: 99%
“…In order to approach amplitude reduction ratio provided by open trenches, different in-filled material has been tested. In particular, in [9][10][11] geofoam (expanded polystyrene or extrude polystyrene) as in-filled materials has been studied, while in [12,13] the use of gas cushions trenches as wave barriers is analyzed, obtaining results very close to open trenches performances.…”
Section: Introductionmentioning
confidence: 99%